The Effect Of Interest Rates And Profit Sharing Ratios On The Collection Of Third Party Funds - Rohansyah, Miswar; Yanti, Yanti; Mongkito, Abdul Wahid; Toar, Alfian; Abdul Rahman, Nik Adzrieman bin (LP2M IAIN Palopo, 2023)
Third Party Funds (DPK) at Sharia Commercial Banks (BUS) are funds sourced from the wider community collected by the bank through the products offered such as savings, deposits and current accounts based on sharia principles. The movement of third party funds can be influenced by several external and internal factors rather than the bank itself. This research aims to test whether the interest rate and profit sharing ratio have an effect on the collection of third party funds in Islamic commercial banks that have registered with OJK for the 2015-2021 period partially and simultaneously. This research is research quantitative, the data source uses secondary data in the form of 84 time series sample. The method used in this research is a multiple linear regression method with the help of the SPSS version 25 program. Partial research results (t test) show that the variable, the interest rate, has a negative and significant effect on third party funds and the profit sharing ratio variable has a positive and positive effect. significant impact on third party funds. Simultaneously (f test) shows that the interest rate and profit sharing ratio influence third party funds in Islamic commercial banks in Indonesia.